Distinct subsets of syt-IV/BDNF vesicles are sorted to axons versus dendrites and recruited to synapses by activity - Dean, Camin; Staudt, Thorsten M.; Engelhardt, Johann; Hell, Stefan (The journal of neuroscience, 2012)
BDNF plays a critical role in the regulation of synaptic strength and is essential for long-term potentiation, a phenomenon that underlies learning and memory. However, whether BDNF acts in a diffuse manner or is targeted to specific neuronal subcompartments or synaptic sites to affect circuit function remains unknown. Here, using photoactivation of BDNF or syt-IV (a regulator of exocytosis present on BDNF-containing vesicles) in transfected rat hippocampal neurons, we discovered that distinct subsets of BDNF vesicles are targeted to axons versus dendrites and are not shared between these compartments. Moreover, syt-IV- and BDNF-harboring vesicles are recruited to both presynaptic and postsynaptic sites in response to increased neuronal activity. Finally, using syt-IV knockout mouse neurons, we found that syt-IV is necessary for both presynaptic and postsynaptic scaling of synaptic strength in response to changes in network activity. These findings demonstrate that BDNF-containing vesicles can be targeted to specific sites in neurons and suggest that syt-IV-regulated BDNF secretion is subject to spatial control to regulate synaptic function in a site-specific manner.
Gesehen am 29.10.2018